Degradation of mechanical properties of CA mortar caused by calcium leaching. (30th May 2019) - Wang, Yong; Yuan, Qiang; Deng, Dehua
Highlights: The leaching kinetics and related changes in mechanical behavior and microstructure of CA mortar were studied. Three distinct zones in term of local calcium content in the direction of radius of the specimen were found. Compressive behavior was modelled by the combination of compression damage model degradation damage model. Abstract: Calcium leaching is an important durability problem for cement asphalt (CA) mortar used in ballastless slab track. In this paper, calcium leaching in CA mortar was accelerated by immersing in 6 mol/L ammonium nitrate solution. The leaching kinetics and related changes in mechanical behavior and microstructure of CA mortar were studied. Results showed that calcium leaching followed the Fick's law. The calcium leaching led to the formation of three distinct zones in term of local calcium content in the direction of radius of the specimen. Due to the leaching of calcium hydroxide and the progressive decalcification of CSH, the three zones had different chemical compositions. The compressive mechanical behavior was modeled by a compression damage model derived from Weibull distribution. The degradation damage model was established on the distribution of local elastic modulus. The combination of these two models can well predict the compressive behavior of partially leached CA mortar.